Analisis Kebijakan Kredit Usaha Pada Bank BRI Kantor Cabang Pembantu Mega Mas Manado - karauwan, febry (ACTA DIURNA KOMUNIKASI, 2012)
Analisis Kebijakan Kredit Usaha Pada Bank BRI Kantor Cabang Pembantu Mega Mas Manado Oleh: Febri Karauwan Abstract : Credit service activities are considered very important and strategic role in the banking indesti credit management resulted in a point of major concern for management in which the main goal is to bank credit management can maximize the performance of the health of the banks themselves by increasing the quantity and quality of credit. Object of this study, namely. Bank Rakyat Indonesia (Persero) Tbk. Branch Office Mega Mas Manado with quantitative data collection techniques with direct interviewing. In 2009 to 2011 amounted to 125 debtors and debtors are 5 traffic, from 125 debtors can be grouped that from 2009 to 2011 BRI Branch Office received 89 Mega Mas Manado borrowers in loans classified as medium and 36 borrowers in the grade a great credit. Bank BRI Branch Office Mega Mas manado turns way better analyze the debtor's financial cukub because from 2009 to 2011 only 5 are jammed even then not include an auction, it is better than the first specialized bank AO (Officer acount) more careful in credit control. Keywords: Business KebijakanKredit